Neurodevelopmental Disorders in Sub‐Saharan Africa: A Survey on Primary Healthcare Workers' Knowledge - Noah Agbo; Yetunde Adeniyi; Onoja Matthew Akpa; Olayinka Omigbodun (Health Science Reports)
ABSTRACT Background Neurodevelopmental disorders are a set of conditions that appear early in a child's development, usually before they begin school, and are likely to impair personal, social, academic, or occupational functioning. These conditions are the result of disturbances in brain development caused by genetic, environmental, or rather unknown causes. With the increasing prevalence of neurodevelopmental disorders in low‐ and middle‐income countries such as Nigeria, it is imperative to understand the level of knowledge of primary healthcare workers who, by virtue of being nearest to the people in the community, are the first point of contact for individuals and families seeking healthcare in the community. This study aimed to assess primary healthcare workers' knowledge level about children and adolescents with neurodevelopmental disorders in Abuja, Nigeria. Methods This was a cross‐sectional study where 274 primary healthcare workers (mean 39.8 ± 10.1 years) were recruited from 17 urban and rural primary healthcare centers (PHCs) in Abuja, Nigeria. The Modified Knowledge and Attitude Towards Child and Adolescent Mental Disorders questionnaire was employed to examine knowledge of and attitudes towards children with disorders (ASD, ADHD, and ID), and the data obtained were analyzed. Percentages and frequencies were used to describe the socio‐demographic characteristics of the respondents as well as the knowledge of the respondents in the study. Means and standard deviations were used to present continuous data, while Chi‐square was used to investigate the association between categorical variables. Results Results from the analysis showed that even with longer working experience of 12.4 ± 6.6 years, respondents had poor knowledge of the identification and management of children and adolescents with neurodevelopmental disorders. A significant majority (68.2%) of the respondents agreed that neurodevelopmental disorders in children and adolescent is a result of weak genes that were passed down to them by their parents. Similarly, 89.4% of the respondents report that imbecile and moron are types of neurodevelopmental disorders found in children. Further, (43.1%) of the respondents believe that supernatural power can be used to inflict neurodevelopmental disorders on children and adolescents. Of the 274 respondents in this study, 182 were Primary healthcare workers from rural/village PHCs. Conclusion Primary healthcare workers demonstrated poor or low knowledge of neurodevelopmental disorders. On‐the‐job training (including continuing medical education), retraining, and an upgrade to the school of health curriculum are adjustments relevant to increasing the awareness and knowledge level of primary healthcare workers in identifying and managing children and adolescents with neurodevelopmental disorders.